2018
DOI: 10.3389/fphys.2018.01590
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Cardiorespiratory Function During Cardiopulmonary Exercise Testing in Untreated Hypertensive and Healthy Subjects

Abstract: Objective: This study aimed to compare differences in cardiorespiratory function between untreated hypertensive subjects (UHS) and healthy subjects (HS) during cardiopulmonary exercise testing (CPET). Additionally, it also aimed to explore the potential mechanisms of different exercise responses in cardiorespiratory function before, during and after CPET.Methods: Thirty subjects (15 UHS and 15 HS) were enrolled. Photoplethysmography (PPG), respiratory signal, and ECG were simultaneously collected while subject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Acute intervention is an effective method of investigating the peripheral hemodynamic parameter responses to external stimuli (Liu et al, 2015;Zhang et al, 2018). Michaels (2002) found that average peak velocity significantly increased during EECP, and coronary flow showed a 28% increase during EECP compared with baseline.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute intervention is an effective method of investigating the peripheral hemodynamic parameter responses to external stimuli (Liu et al, 2015;Zhang et al, 2018). Michaels (2002) found that average peak velocity significantly increased during EECP, and coronary flow showed a 28% increase during EECP compared with baseline.…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies focused on the acute effect of EECP on carotid hemodynamics. Moreover, the mechanisms of acute responses, which can highlight the responses of cardiovascular disease, have not yet been clarified (Levenson et al, 2007;Zhang et al, 2007Zhang et al, , 2018.…”
Section: Introductionmentioning
confidence: 99%
“…These aforementioned studies have demonstrated that TF characteristics are associated with hemodynamic parameters, such as blood flow and blood pressure. Dynamic changes can promote responses in blood pressure, blood velocity, and blood flow 21 . EECP increases peak limb blood flow and improves endothelium-dependent vasodilation in peripheral resistance arteries 22 .…”
Section: Discussionmentioning
confidence: 99%
“…EECP may provide a kind of "exercise massage" on peripheral function, starting from the elastic conduit arteries, the muscular conduit arteries, and extending to the skeletal muscle resistance arteries. 25 A previous study had found that the response to exercise is an effective way to characterize differences in cardiorespiratory function between untreated hypertensives and healthy controls, and to provide useful predictive and diagnostic information for CVD 21 . The peripheral artery features showed no significant differences between hypertensive subjects and controls at baseline, but showed marked changes immediate after exercise 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Acute exercise intervention can effectively highlight the response of cardiovascular function ( Zhang et al, 2018 ). Liu et al (2015) investigated the acute effects of cycling intervention on carotid arterial hemodynamics between basketball athletes and controls.…”
Section: Introductionmentioning
confidence: 99%